Effects of 7-day intake of hydrogen-rich water on physical performance of trained and untrained subjects - Rafael Timón; Guillermo Olcina; Adrian González-Custodio; Marta Camacho-Cardenosa; Alba Camacho-Cardenosa; Ismael Guardado (Termedia Publishing House, 2020)
Hydrogen-rich water (HRW) is used as a supplement to improve performance and reduce fatigue in athletes. However, the potentially beneficial effects of HRW intake could be mediated by the training status of athletes. The purpose of the study was to analyse the ergogenic effect of intake of HRW for one week on aerobic and anaerobic performance, both in trained and untrained individuals. Thirty-seven volunteers participated in the study and were divided into two experimental groups: trained cyclists and untrained subjects. A doubleblind crossover design was performed in which all subjects took a placebo (PW) and nano-bubble HRW (pH: 7.5; hydrogen concentration: 1.9 ppm; oxidation-reduction potential (ORP): -600 mV). At the end of 7-day intake, performance was assessed by an incremental VO2max test and by a maximum anaerobic test. After HRW intake, only trained cyclists improved their performance in the anaerobic test with an increase in peak power (from 766.2 ± 125.6 to 826.5 ± 143.4 W; d = .51) and mean power (from 350.0 ± 53.5 to 380.2 ± 71.3 W; d = .51), and a decrease in the fatigue index (from 77.6 ± 5.8 to 75.1 ± 5.9%; d = .45). The findings demonstrate that the ergogenic effect of HRW is mediated by the training status, and that 7-day intake of HRW would be an effective strategy for improving anaerobic performance in trained cyclists.